Thermal Bending Of Copper Cooling Staves In Blast Furnaces - Cameron Soltys; Maher Al-Dojayli; Hamid Ghorbani (Associacao Brasileira de Metalurgia, Materiais e Mineracao, 2019)
Cooling staves in blast furnaces are used to minimize the process heat loads on steel shell and refractory system. Copper staves are exposed to significant fluctuating thermal loads which may lead to premature stave failures due to cracks, water leakage, bending, abrasion and resultant wear. In this paper, an assessment methodology is presented to evaluate the effect of thermal cycling on copper staves including bending, fatigue and thermal ratcheting. This approach incorporates temperature-dependent copper properties including creep and plasticity to more accurately capture inelastic deformations, damage and fatigue in staves under transient and cyclic thermal loading conditions. Root cause failure assessment and improvements to copper stave design can be assessed using the presented methodology.